Gestational Folate and Folic Acid Intake among Women in Canada at Higher Risk of Pre-Eclampsia. Issue 7 (13th April 2021) - Rose, Elaine G; Murphy, Malia S Q; Erwin, Erica; Muldoon, Katherine A; Harvey, Alysha L J; Rennicks White, Ruth; MacFarlane, Amanda J; Wen, Shi Wu; Walker, Mark C
ABSTRACT: Background: Periconceptional folic acid (FA) supplementation is recommended to prevent neural tube defects; however, the extent to which recommendations are met through dietary sources and supplements is not clear. Objectives: Our objective was to evaluate the dietary and supplemental intakes of FA in a Canadian pregnancy cohort and to determine the proportions of pregnant women exceeding the Estimated Average Requirement (EAR) and Tolerable Upper Intake Level (UL). Methods: FACT (the Folic Acid Clinical Trial) was an international multicenter, randomized, double-blinded, placebo-controlled, phase III trial investigating FA for the prevention of pre-eclampsia in high-risk pregnancies. Participants were enrolled from Canadian sites at 8–16 weeks of gestation. Dietary and supplemental FA intake data were collected through participant interviews and FFQs at the time of FACT enrollment. Categorical data were summarized as n (%) and continuous data as median (IQR). Results: This study included 1198 participants. Participants consumed 485 μg dietary folate equivalents (DFE)/d (IQR: 370–630 μg DFE/d) from dietary sources of folate and FA. Through diet alone, 43.4% of participants consumed ≥520 μg DFE/d, the EAR for pregnant individuals. Of the 91.9% of participants who consumed daily FA supplements, 0.4% consumed <400 μg FA/d and 96.0% consumed ≥1000 μg/d, the UL for FA. Median (IQR) total folate intake was 2167 μg DFE/d (2032–2325 μg DFE/d); 95.3% of participants met or exceeded the EAR from all sources, but 1069 (89.2%) participants exceeded the UL. Conclusions: The majority of participants in this Canadian pregnancy cohort did not consume the recommended amount of folate from dietary sources. However, most prenatal supplements contained 1000 μg FA, resulting in the majority of women exceeding the UL. With no additional benefit associated with FA intakes beyond the UL for most women, modification of prenatal supplement formulations may be warranted to ensure women meet but do not exceed recommended FA intakes. FACT was registered at clinicaltrials.gov as NCT01355159 and at isrctn.com as ISRCTN23781770.